The Relationship of Culture and Islam in Fatwa National Sharia Board of Indonesian Ulama Assembly No: 107/Dsn-Muj/X/2016 Concerning Guidelines for Operating Hospital Based on Sharia Principles - simahatie, Mai; Munawarah, Munawarah; Juanda, Reza; Bahri, Halida (PT. Radja Intercontinental Publishing, 2022)
The purpose of this study was to examine the relationship between culture and Islam in the fatwa of the National Sharia Council-Indonesian Ulema Council No: 107/dsn-muj/x/2016 concerning Guidelines for operating hospitals based on sharia principles. This is important to do because the harmony between culture and standardization of quality indicators of sharia hospital services will make sharia hospitals easily accepted in the community.The design of this research is Literature Review or literature review. Literature research is research conducted using literature (library), either in the form of books, notes, or reports on the results of previous research. The results of the research are almost entirely from the fatwa of the National Sharia Council-Indonesian Ulema Council No: 107/dsn-muj/x/2016 concerning Guidelines for operating hospitals based on sharia principles are closely related or in line with eastern Indonesian culture which upholds the culture of shame, the culture of helping , a culture of advising each other and a culture of clean living.